Desenvolvimento, estabilidade físico-química e perfil sensorial de produto cárneo com adição de farinha de folhas de vinagreira (Hibiscus sabdariffa L.) com potencial antioxidante - Nascimento, Neliane Pereira do (2023)
Antioxidants are used to minimize oxidative changes in meats and meat products. While synthetic antioxidants have widespread use in the food industry, in recent years, the demand for natural antioxidants has increased. This study aimed to develop beef burgers with the addition of Roselle leaves (Hibiscus sabdariffa L.) powder and evaluate their stability during storage under refrigeration and freezing. Initially, a market survey on the consumption of unconventional food plants (UFPs) was conducted, followed by the acquisition and characterization of Roselle leaves powder (botanical identification, toxicology, polyphenol content, antioxidant activity, and proximate composition). Subsequently, formulations of beef burgers were prepared without the addition of antioxidants (F1), with the addition of antioxidants (F2), with the addition of 4 g (F3), 8 g (F4), and 16 g of Roselle leaves / kg of burger (F5), and their physicochemical stability was evaluated under refrigeration at 4 ± 1 ºC for 21 days. Based on these results, the research continued with F1, F2, F3, and F4, where their proximate composition, polyphenol bioaccessibility, ABTS antioxidant activity, SEM, color, texture profile, microbiological analysis, and sensory evaluation were carried out. Finally, the assessment of physicochemical stability under freezing at -18 ± 1ºC for 120 days was conducted. Analysis of variance (ANOVA) was performed for F-test, and means comparison was done by Tukey's test at a 5% significance level. It was observed that the age and education of the participants showed a positive correlation with knowledge and interest in UFPs. Roselle leaves showed no toxicity, being a source of carbohydrates, proteins, and polyphenols, with antioxidant activity against the ABTS radical. The addition of Roselle led to an increase in ash and polyphenol content, making the samples less red compared to F1 but did not interfere with the food matrix, as observed in micrographs and hardness, gumminess, and chewiness parameters. In vitro digestion improved polyphenol bioaccessibility and antioxidant activity against the ABTS radical in the samples. Sensory-wise, the formulations showed overall acceptance between indifferent and liked. The addition of Roselle was associated with the terms "brownish-green color" and "residual flavor." The formulations remained stable under refrigeration and freezing, with F3 obtaining the best results under refrigeration and comparing favorably to F2 for 90 days of frozen storage in relation to lipid oxidation. The results are promising regarding consumer interest in incorporating UFPs into their diet, the sensory acceptance of formulations, and the effect on lipid oxidation control.